THE EFFICENCY OF A MANUAL CHAINSAW PERFORMING UTILIZATION OPERATIONS OF POPLAR TREES IN ZAKHO, KURDISTAN REGION OF IRAQ - Taha, Mohammedamin Y. (Science Journal of University of Zakho, 2024)
In Poplar plantations, manual tree harvesting techniques (using chainsaws) are still utilized, especially on gentle terrain or for smaller trees, where automated felling may not be a possible or safe option. The most important variables affecting the productivity of motor-manual felling, a global survey show that terrain slope, understory density, distance to trees, and diameter at breast height (DBH) are the most major variables influencing the productivity of manual tree felling. In harvesting activities like felling, delimbing, and bucking, skilled workers are required. Chainsaw use is associated with timber harvesting activities including felling, delimbing, and bucking in forest areas. The chainsaw felling hourly output was 0.4546 m3/h, the delimbing hourly production was 0.482 m3/h, and the bucking hourly production was 0.753 m3/h. As tree DBH increased, chainsaw productivity also increased. In the present study, the utilization rate and chain saw productivity hours (PMH) were 8.25 hours and 71%, respectively. Regression models’ calibration and validation procedures for many aspects of tree utilization were used to develop the mathematical models between the above-mentioned process included in utilization as dependent variables and both DBH and total height of trees as independent variables. The coefficient of determination was used to test the efficiency of the calibration and validation of the developed models in the estimation of the dependent variables, the most acceptable Equation No. 11 with a 91.86 coefficient of determination(R2). Planning for sustainable harvesting can be influenced by the primary suggestions for improving motor-manual felling productivity.